2021
DOI: 10.34172/hpp.2021.37
|View full text |Cite
|
Sign up to set email alerts
|

Systematic evaluation of COVID-19 related Internet health rumors during the breaking out period of COVID-19 in China

Abstract: Background: To adapt the scientific evaluation tool for the confusion evaluation of health rumors and to test this tool to the confusion evaluation of coronavirus disease 2019 (COVID-19)-related health rumors on Chinese online platforms during the outbreak period of COVID-19in China. Methods: The design of our study was systematic evaluation of COVID-19-related health rumors. Retrieved from 7 rumor-repellent platforms, rumors about COVID-19 were collected during the publication from December 1, 2019, to Februa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In current practice, rumor management of public health emergencies mainly starts with regulators and media, using traditional means such as deleting posts, dispelling rumors and media guidance ( 8 ). And the public often tends to search for more information to reduce uncertainty in a chaotic environment, which leads to the great spread of rumors ( 10 , 11 ). Numerous studies have indicated the pronounced significance of stakeholder-oriented governance concerning rumors within the domain of public health incidents ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…In current practice, rumor management of public health emergencies mainly starts with regulators and media, using traditional means such as deleting posts, dispelling rumors and media guidance ( 8 ). And the public often tends to search for more information to reduce uncertainty in a chaotic environment, which leads to the great spread of rumors ( 10 , 11 ). Numerous studies have indicated the pronounced significance of stakeholder-oriented governance concerning rumors within the domain of public health incidents ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to thinking space, people with Cyber-Syndrome are more likely to feel loneliness, depression, and anxiety. For example, Shekar and Aravantagi [34] pointed out that there was a strong relationship between overwhelming online information and anxiety. The easily available online information played a catalytic role in anxiety particularly during COVID-19.…”
Section: Cyber-enabled Symptoms Of Cyber-syndromementioning
confidence: 99%
“…The World Health Organization carried out a series of communication campaigns to combat the spread of misinformation on the spread of the COVID-19 disease and the information epidemic in 2021 [13][14][15]. In particular, among rumors generated by public health crises, the proportion of health rumors is higher and the social impact is more serious [16]. In China, epidemic-related rumors in 2020, including "COVID-19 is a biological weapon" and "Shuang-Huang oral liquid can treat COVID-19," consecutively emerged on social media platforms, including WeChat and Weibo, and subsequently filled the cyberspace, causing panic to the public [17].…”
Section: Harms Of Health Rumorsmentioning
confidence: 99%